Chronic insomnia: are patients also suffering from PTSD symptoms? - Lardant, Emma; Vialatte, François; Ramdani, Céline; Chauveau, Frédéric; Gauriau, Caroline; Storms, Léna; Trousselard, Marion; Léger, Damien (Frontiers in Sleep, 2023)
Insomnia is highly prevalent in the general population, and is commonly associated with somatic and psychiatric comorbidities. However, its origins remain poorly-understood. Recently, adverse childhood events (ACE), including traumatic experiences, have been found to be significantly associated with both insomnia and Post-Traumatic Stress Disorders (PTSD). Many patients with PTSD suffer from sleep disorders. However, we know much less about traumatic childhood experiences in patients with insomnia and PTSD. Our exploratory study investigated a cohort of 43 patients (14 males, 29 females) clinically diagnosed with chronic insomnia at a sleep center, and systematically evaluated their condition using the trauma history questionnaire (THQ), and the PTSD checklist (PCL-5). Our results show that 83.72% of insomnia patients reported at least one traumatic event, while the prevalence of PTSD symptoms was 53.49%. For 11.6% of patients, insomnia began in childhood, while for 27.07% it began in adolescence. PCL-5 scores were associated with higher Insomnia Severity Index (ISI) scores, but not trauma. ISI scores were also higher for women, and positive relationships were observed between ISI scores, PCL-5 scores and the number of self-reported traumatic events among women. These exploratory results highlight that the relationship between PTSD symptoms and insomnia could be sex-specific. They also highlight the importance of PTSD symptoms screening for patients diagnosed with chronic insomnia.